King for a day - Khan, Rukhsana, 1962- (Lee & Low Books, Inc., 2013)
"Even though he is confined to a wheelchair, a Pakistani boy tries to capture the most kites during Basant, the annual spring kite festival, and become "king" for the day. Includes an afterword about the Basant festival"--Provided by publisher.